Listeners' guide to classical music : an introduction to the great classical composers and their works - Mcleish, Kenneth (Longman, 1986)
In this volume, the authors offer helpful suggestions on where to begin, what to expect and what to hear next, making this an invaluable starting point from which to explore the whole range of classical music. Their selection of one hundred composers and two dozen types of music includes the finest and most enjoyable in the repertoire while their non-technical descriptions illustrate just how the music reflects the composers' lives and the time for which it was written. Over 1000 individual works are covered, accompanied by follow-up listening suggestions and recommendations.